Fused Lateral Clitoral Hood and Labia Minora: New Classification Based on Anatomic Variation of the Clitoral Hood–Labia Minora Complex and Simple Surgical Management. (21st February 2022) - Xia, Zenan; Liu, Chang-Yi; Zhang, Mingzi; Zhang, Yuwei; Guan, Ai; Li, Yunzhu; Yu, Nanze; Liu, Zhifei; Zeng, Ang; Si, Loubin; Long, Fei; Long, Xiao; et al.
Abstract: Background: Existing classifications of the clitoral hood–labia minora complex (CLC) have neglected its integrity and anatomic variation, resulting in failure to optimize approaches tailored to individuals. Objectives: The aim of this study was to present a new classification system for comprehensive evaluation of variations of the CLC and to introduce a simple surgical approach for the fused type. Methods: Anatomic variations of the CLC were classified into 3 types: isolated labia minora or lateral clitoral hood hypertrophy (Type 1); conventional combined hypertrophy (Type 2); and fused lateral clitoral hood and labia minora (Type 3). A modified procedure for the fused type was performed in 4 steps: the anterior border of labia minora was defined first, then the hypertrophic lateral clitoral hood and labia minora were each removed separately, and finally the junction region was trimmed. Satisfaction questionnaires were administered during follow-ups. Results: Among all 301 patients (602 sides), Type 2 was the most common variation (285 sides, 47.3%). Type 3 variations in 67 patients (105 sides, 17.5%) were identified, and 77.6% of these patients answered the questionnaires 3 months after surgery. For patients with type 3 variations, the satisfaction rate in the 4-step excision group was 91.7%, which was significantly higher than that in the wedge excision group (56.3%) ( P  = 0.01). The complication rate of the 4-step excision was 2.5%. Conclusions: Preoperative evaluation based on the new classification facilitated recognition of variations of the CLC, especially of the fused type. The 4-step excision is a simple, effective, and safe approach to treat the fused variation with high satisfaction. Level of Evidence: 4: